Complete genome sequence of Thermosphaera aggregans type strain (M11TLT). Issue 3 (May 2010) - Spring, Stefan; Rachel, Reinhard; Lapidus, Alla; Davenport, Karen; Tice, Hope; Copeland, Alex; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; Bruce, David; Goodwin, Lynne; et al.
Abstract Thermosphaera aggregans Huberet al. 1998 is the type species of the genusThermosphaera, which comprises at the time of writing only one species. This species represents archaea with a hyperthermophilic, heterotrophic, strictly anaerobic and fermentative phenotype. The type strain M11TLT was isolated from a water-sediment sample of a hot terrestrial spring (Obsidian Pool, Yellowstone National Park, Wyoming). Here we describe the features of this organism, together with the complete genome sequence and annotation. The 1, 316, 595 bp long single replicon genome with its 1, 410 protein-coding and 47 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.